The impact of crankcase oil containing phosphorus on catalytic converters and engine exhaust emissions - Kaleli, H (MCB U P LIMITED, 2001)
Two 10W30 mineral-base phosphorus containing (commercial) and phosphorus-free (P-Free) crankcase oils were tested in the engine dynamometer for the poisoning effects on a catalytic converter and emission-engine's performance. The emission results of the two oils were compared with and without a catalytic converter, including the light-off temperature of the catalyst. Surface characterisation was used to determine accumulated catalyst poisoning from the oil additives. The performance analysis shows that the catalytic converter lowers the torque and power for the commercial and P-Free oils, whereas the specific fuel consumption increases for both oils in the presence of the catalytic converter. In both cases of the presence and the absence of catalytic converter the torque, power and specific fuel consumption remain the same for phosphorus containing and P-Free oils. The presence of the catalytic converter shows lower HC and CO and higher CO2 emissions for both P-Free and commercial oils. Surface characterisation using x-ray microanalysis techniques of Scanning Electron Microscopy and indicated residual amounts of poisons, predominantly P, Ca, S and Zn deposited on the catalyst.
Keywords: emissions; oil; engines; performance measurement; HYDROCARBON EMISSIONS; IGNITION; Engineering